ANALISIS PERBANDINGAN GELAGAR INDUK JEMBATAN KONSTRUKSI BALOK BETON KONVENSIONAL DENGAN GIRDER BAJA KOMPOSIT JEMBATAN AIR PEDU OKI - Sartika Nisumanti; Djaenudin Hadiyana (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
Economic conditions in South Sumatera Province are developing, the Government made policy by opening a new alternative rute from Palembang to Kayu Agung, Ogan Komering Ilir Regency, so the vehicles going towards Kayu Agung or otherwise can use this rute. Therefore, the construction of Air Pedu bridge that connects Jakabaring Palembang - Jejawi road with a length of 25 meters were done. The problem is the construction of the Pedu Water Bridge are use 5 prestress precast girder beams that are 1.25 meters high so that the mobilization to the location is quite difficult, so it is try to be re-planned by using conventional concrete beams which are casted on the spot and also try to be re-planned by using composite steel. Thus the bridge is planned by using conventional concrete beams and steel girder beams. The aims to compare the results of the calculation of the longitudinal girder of Air Pedu Bridge using material and concrete prestress calculation method by re-planning using the method of calculation of conventional concrete beams and steel girder beams by re-planning both methods with reference to applicable planning standards.The result is the loading of conventional concrete beams by using the quality of concrete fc’= 4000 psi and reinforcing steel fy = 40000 psi gained a moment Mu=3879,6 k-ft, and rmax = 0,0371. Loading girder beam with steel profile Bj 37 with ¦y = 240 Mpa and ¦u = 370 MPa got the total moment Mtot = 394,01 t.m. From the results of calculations Conventional concrete beams and steel girder beams still allow for bridges with short spans, especially spans 25 meters.Keywords : conventional concrete girder, composite steel grider, prestressed concrete